Spray-drying and extrusion processes: Effects on morphology and physicochemical characteristics of starches isolated from Peruvian carrot and cassava - dos Santos, Thais Paes Rodrigues [UNESP]; Franco, Célia Maria Landi [UNESP]; Demiate, Ivo Mottin; Li, Xue-Hong; Garcia, Emerson Loli [UNESP]; Jane, Jay-lin; Leonel, Magali [UNESP] (Elsevier, 2018)
The Peruvian carrot and cassava starches were processed by spray-drying and extrusion processes. The amylose content, molecular weight of amylopectin, morphology, granule size, crystalline fraction, and thermal and pasting properties were investigated and compared with those native starches. The spray-dried starches showed reduction on molecular weight of amylopectin and reduction on crystallinity. This process caused change in surface granules as folds and wrinkles, and consequence reducing in granule size, when compared to native starch. There were partial gelatinization of spray-dried starches, with the development of viscosity at room temperature. The Peruvian carrot starch was most susceptible by spray-drying process. Extruded starch showed great reduction on molecular weight and complete degradation on crystalline fraction. The surface morphology of these starches showed a melting mass, due to the fully gelatinization. With these unique properties induced by both processes, the possibilities of industrial applications of these starches are significantly increased.
Keywords: Gelatinization; Molecular weight; Thermal and pasting properties